2006
DOI: 10.1108/02686900710715620
|View full text |Cite
|
Sign up to set email alerts
|

Investors' attitudes toward source credibility

Abstract: Purpose -To inform research on source credibility by providing insight into investors' perception and use of common information sources. Design/methodology/approach -In total, 235 individuals with investing experience or intent ranked the perceived credibility of nine common sources that report unaudited corporate earnings estimates and nine sources of non-financial performance measures. Respondents also assessed the relative value of source credibility to their investment decisions and indicated which common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
(25 reference statements)
0
12
0
2
Order By: Relevance
“…Regarding CMS assurance, it is likely that the individually perceived credibility of an assurer by company stakeholders, for example, capital providers, is influenced by the group‐related perceived credibility of the class of assurance provider, for example, audit firms. Consequentially, investigating the class of CMS assurance providers and its credibility seems reasonable (Schwarzkopf, 2007). Possibly, information stemming from audit firms is perceived as more credible.…”
Section: Background Prior Research and Hypotheses Developmentmentioning
confidence: 99%
“…Regarding CMS assurance, it is likely that the individually perceived credibility of an assurer by company stakeholders, for example, capital providers, is influenced by the group‐related perceived credibility of the class of assurance provider, for example, audit firms. Consequentially, investigating the class of CMS assurance providers and its credibility seems reasonable (Schwarzkopf, 2007). Possibly, information stemming from audit firms is perceived as more credible.…”
Section: Background Prior Research and Hypotheses Developmentmentioning
confidence: 99%
“…We deem a student sample appropriate, because this group is still relatively unfamiliar with investing (i.e., the investment experience of respondents who had invested before, or 26.6% of the sample, averages 3.1 years online and 3.8 years offline), but their potential revenues are high. Indeed, Schwarzkopf (2007) showed that business students are frequently involved with investing or planning to do so in the future. In addition, it has been shown that TBSS adopters are usually relatively young, highly educated consumers (Meuter et al 2003).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Twenty-one percent of the respondents are already a customer of the service provider. Schwarzkopf (2007) shows that business students are often investing small amounts in stocks or planning to do so in the near future. Furthermore, early adopters of these types of complex online services are usually relatively young, highly educated consumers (Meuter et al 2003).…”
Section: Samplementioning
confidence: 99%